Achievements and Issues in Sustainable Development in Nepal - Sharma, Gyanendra Raj (Journey for Sustainable Development and Peace Journal, 2023)
By conducting a comprehensive literature study on viewpoints regarding sustainability and development, this research aims to synthesize the accomplishments and challenges associated with sustainable development. The study utilizes a review-based methodology that is based on discussions and debates among academics, scholars, and philosophers. In order to advance development narratives, sustainable development (SD) necessitates achieving a harmonious balance among three fundamental pillars: social, economic, and environmental. The literature draws the conclusion that SD has emerged around three fundamental concepts. Based on the available evidence, it can be firmly concluded that sustainability represents the sole viable pathway for achieving sustainable development. This entails the integration of profound contemplation, responsible actions, and the assimilation of valuable lessons from diverse successful practices on a global scale. While acknowledging the praiseworthy achievements resulting from historical endeavors and recent initiatives such as Agenda 2030 and the Sustainable Development Goals, it is essential to recognize the imperative of addressing the existing challenges to enhance the overall effectiveness and comprehensiveness of sustainable development efforts.